New Insights Into the Regulation of Natural-Killer Group 2 Member D (NKG2D) and NKG2D-Ligands: Endoplasmic Reticulum Stress and CEA-Related Cell Adhesion Molecule 1 - Hosomi, Shuhei; Grootjans, Joep; Huang, Yu-Hwa; Kaser, Arthur; Blumberg, Richard S. (Frontiers in Immunology, 2018)
Natural-killer group 2 member D (NKG2D) is a well-characterized activating receptor expressed by natural killer (NK) cells, NKT cells, activated CD8+ T cells, subsets of γδ+ T cells, and innate-like T cells. NKG2D recognizes multiple ligands (NKG2D-ligands) to mount an innate immune response against stressed, transformed or infected cells. NKG2D-ligand surface expression is tightly restricted on healthy cells through transcriptional and post-transcriptional mechanisms, while transformed or infected cells express the ligands as a danger signal. Recent studies have revealed that unfold protein response (UPR) pathways during endoplasmic reticulum (ER) stress result in up-regulation of ULBP-related protein via the PERK-ATF4-CHOP pathway, which can be linked to the pathogenesis of autoimmune diseases. Transformed cells however possess mechanisms to escape NKG2D-mediated immune surveillance, such as upregulation of carcinoembryonic antigen (CEA)-related cell adhesion molecule 1 (CEACAM1), a negative regulator of NKG2D-ligands. In this review, we discuss mechanisms of NKG2D-ligand regulation, with a focus on newly discovered mechanisms that promote NKG2D-ligand expression on epithelial cells, including ER stress, and mechanisms that suppress NKG2D-ligand mediated killing of cancer cells, namely by co-expression of CEACAM1.